12
$\begingroup$

For some time I've been playing with this kind of sums, for example I was able to find that $$ \frac{\pi}{2}=1+2\sum_{k=1}^{\infty}\left( \zeta(2k+1)-\beta(2k+1)\right) $$ where $$ \beta(x)=\sum_{k=1}^{\infty}\frac{(-1)^{k-1}}{(2k-1)^{x}} $$ is the Dirichlet's beta function and $\zeta(x)$ is the Riemann's zeta function. I find this result very interesting, because we know that for odd integers $\beta(x)$ reduces to $$ \beta(2k+1)=(-1)^{k}\frac{E_{2k}\pi^{2k+1}}{4^{k+1(2k)!}}. $$
Where $E_{2k}$ are the Euler's numbers: $$ \begin{matrix} E_{0} &=& 1\\ E_{2} &=& -1\\ E_{4} &=& 5\\ E_{6} &=& -61\\ E_{8} &=& 1385\\ \vdots &=&\vdots \end{matrix} $$ But there is no known similar simple relation for $\zeta(2k+1)$. Nevertheless, when both are combined they give the above beautiful result.

Now, I'd like to know if there is something similar for $$ \sum_{k=1}^{\infty}\left( \zeta(2k)-\beta(2k)\right) $$ Any help would be appreciated.

Thanks.

$\endgroup$
  • 1
    $\begingroup$ What exactly is $E_{2k} \pi^{2k+1}$? $\endgroup$ – john_leo Oct 26 '14 at 13:01
10
$\begingroup$

There is a closed form for your series:

$$ \sum_{k=1}^{\infty}\left( \zeta(2k)-\beta(2k)\right)=\frac{1}{2}+\frac{1}{2}\ln2. \tag1 $$

Proof. Using absolute convergence of the series, you may write

$$\begin{align} \sum_{k=1}^{\infty}\left( \zeta(2k)-\beta(2k)\right) & = \sum_{k=1}^{\infty}\left( \sum_{n=1}^{\infty}\frac{1}{n^{2k}}-\sum_{n=1}^{\infty}\frac{(-1)^{n-1}}{(2n-1)^{2k}}\right)\\\\ & = \sum_{k=1}^{\infty}\left( \sum_{n=\color{red}2}^{\infty}\frac{1}{n^{2k}}-\sum_{n=\color{red}2}^{\infty}\frac{(-1)^{n-1}}{(2n-1)^{2k}}\right)\\\\ & = \sum_{n=2}^{\infty}\left( \sum_{k=1}^{\infty}\frac{1}{n^{2k}}-\sum_{k=1}^{\infty}\frac{(-1)^{n-1}}{(2n-1)^{2k}}\right)\\\\ & = \sum_{n=2}^{\infty}\left( \frac{1}{n^{2}}\frac{1}{1-\frac{1}{n^{2}}}+\frac{(-1)^{n}}{(2n-1)^{2}}\frac{1}{1-\frac{1}{(2n-1)^{2}}}\right)\\\\ & = \sum_{n=2}^{\infty}\frac{1}{(n+1)(n-1)}+\sum_{n=2}^{\infty}\frac{1}{8n(2n-1)}-\sum_{n=2}^{\infty}\frac{1}{8(2n-1)(n-1)}\\\\ & = \frac{1}{2}+\frac{1}{2}\ln2, \end{align}$$ where, in the last steps, we have used partial fraction decomposition, telescoping terms and a familiar series for $\ln 2$.

$\endgroup$
2
$\begingroup$

Hint: Rewrite the general term as an infinite series, and then switch the order of summation. :-$)$

$\endgroup$
1
$\begingroup$

$$ \begin{align} \color{red}{S}\,&=\sum_{n=1}^{\infty}\left[\,\zeta(2n)-\beta(2n)\,\right] =\sum_{n=1}^{\infty}\frac{\Gamma(2n)\zeta(2n)-\Gamma(2n)\beta(2n)}{(2n-1)!} \\[2mm] &=\int_{0}^{\infty}\left(\frac{1}{e^{x}-1}-\frac{e^{x}}{e^{2x}+1}\right)\left(\sum_{n=1}^{\infty}\frac{x^{2n-1}}{(2n-1)!}\right)\,dx\qquad\color{blue}{\small\left\{\sinh(x)=\sum_{n=1}^{\infty}\frac{x^{2n-1}}{(2n-1)!}\right\}} \\[2mm] &=\int_{0}^{\infty}\left(\frac{e^x+1}{e^{2x}-1}-\frac{e^{x}}{e^{2x}+1}\right)\left(\frac{e^{2x}-1}{2e^{x}}\right)\,dx =\frac{1}{2}\int_{0}^{\infty}\left(1+\frac{1}{e^{x}}-\frac{e^{2x}-1}{e^{2x}+1}\right)\,dx \\[2mm] &=\frac{1}{2}\int_{0}^{\infty}\left(\frac{1}{e^{x}}+\frac{2}{e^{2x}+1}\right)\,dx =\color{red}{\frac{1}{2}\left[\,\Gamma(1)+\eta(1)\,\right]} =\frac{1}{2}\left(1+\log(2)\right) \end{align} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.